Students’ Socio-Economic Status and Their English Achievement in Indonesian Perspective - Rahmayani Rahmayani; Hasnawati Hasnawati; Muh Arief Muhsin (Institut Agama Islam Negeri Palopo, 2022)
Language skills are extremely crucial to grasp in order to face the progress of time. In Indonesia, English is a foreign language and has become part of the school curriculum, from elementary school to university. Parents are their children's first educators, and children grow and develop best in their families. As a result, whether directly or indirectly, the existence of the family has an impact on the learning achievement of children. The purpose of this study was to know and explain the relationship between students’ socio-economic status and their English achievement in the 8th grade students of SMP Muhammadiyah 1 Makassar. The sample for this study consists of 29 students from class A. The information came from a questionnaire about the students' SES, as well as information from the English teacher about students' English achievement and English scores on the odd semester final test. Both of the data sets were calculated with Person Product Moment Correlation in SPSS Program Version 23. Referring to the research question, the result shows that there was a positive significance correlation between students’ socio-economic status (X) and their English achievement (Y). It was found that the correlation value was equal to 0,535, which means the correlation between two variables is moderate (0.40–0.599), it is included in the third category. As the findings showed, rxy>rtable= 0.535 > 0.367. Therefore, it can be concluded that the students’ higher SES had an influence on how their achievement will be measured. For future researchers, the research should be done (if using the same method) with some improvements, such as the type of the questionnaire, number of samples, previous studies, etc. This is expected to show more clearly and comprehensibly the relationship between students’ socio-economic status and their learning achievement